Algebraic Literacy among Pesantren-based Senior High School Students - Utomo, Dwi Priyo; Sulfiah, Sitti Karimah; Inganah, Siti (JTAM (Jurnal Teori dan Aplikasi Matematika), 2022)
Mathematics is a vital means needed by students to solve various problems, both personal and social, and it is required to succeed in work. Thus, students are highly expected to possess good mathematical literacy. In the 21st Century, most of parents would rather choose pesantren-based schools for their children since they believe that theirs will have chance to acquire universal and religious sciences, at once, for their life. Further, the current research was aimed to investigate level of algebraic literacy among pesantren-based senior high school students, along with its determinant factors. Qualitative research method was employed by means of descriptive approach. Moreover, there were 30 students involved in the research; all of which were the twelfth graders of Science Class of a pesantren-based senior high school in Madura, Indonesia. To collect data, two instruments were used: algebraic literacy test and guideline to interview with the Math teacher and the Vice Principal of Curriculum Affairs. The results showed that level of algebraic literacy among students was dramatically low, with 94% of whom classified in below Level 1, 3% in Level 2, and 3% in Level 3. Moreover, lack of student’s focus in learning Mathematics was one of possible causes of it as the students were strongly demanded to learn about two major sciences at once. Therefore, any endeavors for betterment from the teacher and institution are needed to make algebraic literacy among students get improved; one of which can be by integrating pesantren and national education curricula.